2018
DOI: 10.3847/2041-8213/aae20c
|View full text |Cite
|
Sign up to set email alerts
|

HST STIS UV Spectroscopic Observations of the Protoplanetary Nebula Hen3-1475

Abstract: We present UV spectra of the protoplanetary nebula (pPN) Hen 3-1475 obtained with the Space

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The actual jet dynamics within the lobes could be more complex than previously anticipated. An investigation of the multi-epoch HST F658N images suggests that the outer knots (NW2/SE2 and NW3/SE3) of Hen 3-1475 may not be the radially fast-moving "bullets" as previously thought, but locally excited due to Kelvin-Helmholtz instabilities [14]. If this is true, then NW2/SE2 and NW3/SE3 are probably different from NW1/SE1 in terms of formation and excitation.…”
Section: Jet Kinematics and Preliminary Interpretationmentioning
confidence: 89%
“…The actual jet dynamics within the lobes could be more complex than previously anticipated. An investigation of the multi-epoch HST F658N images suggests that the outer knots (NW2/SE2 and NW3/SE3) of Hen 3-1475 may not be the radially fast-moving "bullets" as previously thought, but locally excited due to Kelvin-Helmholtz instabilities [14]. If this is true, then NW2/SE2 and NW3/SE3 are probably different from NW1/SE1 in terms of formation and excitation.…”
Section: Jet Kinematics and Preliminary Interpretationmentioning
confidence: 89%
“…The selfabsorption of X-rays by gas within the nebula considerably reduces the detection of soft X-rays, and this provides a plausible explanation for the lack of detection of X-ray emission in the other parts of the nebula, given the sensitivity of Chandra. Finally, the emission of [NII] and [SII] in Hen 3-1475 (see Fang et al 2018 and references therein) is related to shocked gas of moderate temperatures, and it is likely that they arise from the jets and the forward shock of the bipolar nebula. However, the jets in Hen 3-1475 are broken into bullets of gas, which are a natural consequence of neck instabilities (Jackson 1962).…”
Section: Discussionmentioning
confidence: 99%
“…This article also investigates the self-magnetic collimation of the winds, and we are able to reproduce in general terms two observed objects, HD 101584 (Olofsson et al 2019) observed with the Atacama Large Millimeter Array (ALMA) and Hen 3-1475 (Fang et al 2018) observed with the Hubble Space Telescope (HST), in which the process of self-collimation can be directly observed.…”
Section: Introductionmentioning
confidence: 99%
“…The transformation lasts a few thousand years at most and the PPN is largely obscured until a combination of expansion and dust expulsion brings it into view. In this time, a usually quite spherical shape of the post-AGB envelope may distort into a dynamic display of winds, bullets and jets, creating rings, ellipses, butterflies and funnels, as summarised by Fang et al (2018b). Highresolution images investigated by Corradi & Schwarz (1995) show ∼ 64% of outflows arrive at the PN stage as elliptical.…”
Section: Introductionmentioning
confidence: 99%